Implementasi Quality Assurance Dalam Meningkatkan Mutu Pendidik Dan Tenaga Kependidikan Di Ma Hidayatul Mubtadiin Jati Agung Lampung Selatan - Galuh Ayudya Hadi; Cipto Handoko; An An Andari (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
The primary objective of this study is to analyze the implementation of quality assurance (QA) in improving the quality of educators and education personnel at MA Hidayatul Mubtadiin Jati Agung, South Lampung. This study used a qualitative approach with a case study design to analyze the implementation of quality assurance (QA) in improving the quality of educators and education personnel at MA Hidayatul Mubtadiin, South Lampung. The units of analysis included teachers, education personnel, madrasah principals, and administrative staff. Data were collected through in-depth interviews, participant observation, and document review, such as standard operating procedures (SOPs), evaluation guidelines, and performance reports. Thematic analysis was conducted to identify QA procedures, teacher competency improvement, supervision effectiveness, and collaboration among madrasah members. Data validity was maintained through triangulation and member checking. This study shows that the implementation of quality assurance (QA) at MA Hidayatul Mubtadiin Jati Agung significantly improved the quality of educators and education personnel. QA strengthens teachers' pedagogical competence through regular training, supervision, and performance evaluation, enabling teachers to be more structured in designing teaching materials, selecting learning methods, and evaluating student achievement. Furthermore, QA enhances the professionalism of education personnel through the implementation of standard procedures, work discipline, administrative management, and more effective internal coordination. QA also encourages collaboration and collective participation among madrasah members, creating a culture of professionalism and shared responsibility. These results demonstrate that QA can serve as a model for holistic and sustainable educational quality development that can be replicated in other educational institutions.